A Cross-Cultural View of Iranian Multilingualism: The Case of Azerbaijani Turkish, Persian, Arabic and Kurdish Contact - Shahiditabar, Mostafa; Pourghasemian, Hossein (Global Journal of Social Sciences Studies, 2016)
The study of language in relation to society is defined as sociolinguistic. One of the most important currents of sociolinguistic research focuses on language change since languages as social phenomena have always changed in the past and they defiantly continue to change today. Some social contexts are the places where languages come into contact with each other. Iran as a multicultural country which is replete with numerous languages and dialects brings some non – official languages like Azerbaijani Turkish or Arabic (which are official languages in other countries) into contact with the only official language of Iran namely Persian. The current study aims to consider the multilingual context of Iran and report any probable language changes on the first hand and argue against Rezvani & Asadpour (2008) on the other hand. The framework used in this study is ’change in apparent time’ introduced by Lindguist (2009). Regarding the first part of the study, the results show that the Islamic Revolution of Iran in 1979 has entered some words into the languages investigated in this study mostly Arabic or Islamic terminology. Also, lexical change has been accrued in Kurdish since it borrowed some words from Turkish and Persian. The other finding of the current study is that both Turkish and Persian have exchanged some words thanks to the contact they have. Arabic as the language of Islam has an impact on both Persian and Turkish as well as Kurdish. Regarding the second part of the study, no change has occurred in Turkish structure and what Rezvani & Asadpour (Rezvani & Asadpour, 2008) report about Turkish and Persian for most part is not reliable.